Plerixafor (a CXCR4 antagonist) following myeloablative allogeneic hematopoietic stem cell transplantation enhances hematopoietic recovery. Issue 1 (December 2016) - Green, Michael; Chao, Nelson; Chhabra, Saurabh; Corbet, Kelly; Gasparetto, Cristina; Horwitz, Ari; Li, Zhiguo; Venkata, Jagadish; Long, Gwynn; Mims, Alice; Rizzieri, David; Sarantopoulos, Stefanie; et al.
Abstract Background The binding of CXCR4 with its ligand (stromal-derived factor-1) maintains hematopoietic stem/progenitor cells (HSPCs) in a quiescent state. We hypothesized that blocking CXCR4/SDF-1 interaction after hematopoietic stem cell transplantation (HSCT) promotes hematopoiesis by inducing HSC proliferation. Methods We conducted a phase I/II trial of plerixafor on hematopoietic cell recovery following myeloablative allogeneic HSCT. Patients with hematologic malignancies receiving myeloablative conditioning were enrolled. Plerixafor 240 μg/kg was administered subcutaneously every other day beginning day +2 until day +21 or until neutrophil recovery. The primary efficacy endpoints of the study were time to absolute neutrophil count >500/μl and platelet count >20, 000/μl. The cumulative incidence of neutrophil and platelet engraftment of the study cohort was compared to that of a cohort of 95 allogeneic peripheral blood stem cell transplant recipients treated during the same period of time and who received similar conditioning and graft-versus-host disease prophylaxis. Results Thirty patients received plerixafor following peripheral blood stem cell (n = 28) (PBSC) or bone marrow (n = 2) transplantation. Adverse events attributable to plerixafor were mild and indistinguishable from effects of conditioning. The kinetics of neutrophil and platelet engraftment, as demonstrated by cumulative incidence, from the 28 study subjects receiving PBSC showed faster neutrophil (p = 0.04) and platelet recovery >20 K (p = 0.04) compared to the controls. Conclusions Our study demonstrated that plerixafor can be given safely following myeloablative HSCT. It provides proof of principle that blocking CXCR4 after HSCT enhances hematopoietic recovery. Larger, confirmatory studies in other settings are warranted. Trial registration ClinicalTrials.govNCT01280955